Characterization of one-part alkali-activated slag with rice straw ash. (22nd August 2022) - Yin, Kangting; Jiang, Yaqing; He, Hui; Ren, Jie; Li, Zhenming
Highlights: The fresh and hardened properties of one-part alkali-activated slag (AAS) with rice straw ash (RSA) are investigated. The Si provided by RSA reduces the early-age reaction rate and contributes to the gel growth. The pore structure of one-part AAS becomes coarser upon the addition of RSA. The autogenous and drying shrinkage of one-part AAS are mitigated by RSA mainly due to the internal curing effect of RSA. Abstract: In this paper, fresh (setting and rheology) and hardened properties (strength and shrinkage) of one-part alkali-activated slag (AAS) with and without rice straw ash (RSA) are comprehensively investigated. The reaction kinetics and microstructure of the mixtures are characterized by a series of experimental techniques. The results reveal that RSA plays dual roles in AAS, as a precursor (though not fully reactive) and an internal curing agent. The reactive K and Si in RSA participate in the formation of C-(A)-S-H gel and the alkaline groups dissolved from the ash facilitate the hydrolysis of slag. Besides, the porous RSA absorbs liquid in the first day and releases it afterwards, thus providing internal curing to the matrix. The consistency index of the paste becomes higher with the incorporation of RSA. Both autogenous and drying shrinkage of AAS, which are considered as two problematic issues for this material, are mitigated by RSA.